Cumulative Risk Assessment of Emerging Pollutants in Healthcare Waste: A Novel One-Health Approach to Quantify Long-Term Impacts on Human and Ecosystem Health - Yohanes Fritantus; Hendrikus Hironimus Botha; Dhwany D B (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
Healthcare waste (HCW) is a significant environmental and public health concern due to its hazardous nature, particularly the presence of emerging pollutants such as pharmaceuticals, heavy metals, and pathogens. The improper disposal and management of healthcare waste contribute to pollution and pose long-term risks to both human health and ecosystems. This study examines the toxicity risks associated with HCW in areas near healthcare facilities with inadequate waste management practices, showing an increase in toxicity risks by 22% to 30%. The research develops a cumulative risk assessment model that integrates human exposure with ecological risks, considering both direct and synergistic effects of pollutants. The model incorporates various components, including pollutant analysis, bioaccumulation mapping, and long-term exposure modeling, to assess the environmental and health risks of HCW. The findings highlight that inadequate waste management leads to significant pollutant accumulation in local ecosystems, with direct implications for biodiversity and human health. Additionally, the study emphasizes the benefits of applying the One-Health approach, which considers the interconnectedness of human, animal, and environmental health, offering a more integrated understanding of the risks posed by HCW pollutants. The research advocates for the incorporation of the One-Health model in healthcare waste management policies to mitigate risks and improve sustainability. Future studies should refine the cumulative risk assessment model and expand it to encompass other environmental waste sources, providing a more comprehensive understanding of pollutant impacts and advancing mitigation strategies.